2018
DOI: 10.3389/fchem.2018.00205
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study of the Benzoylformate Decarboxylase Reaction Mechanism

Abstract: Density functional theory calculations are used to investigate the detailed reaction mechanism of benzoylformate decarboxylase, a thiamin diphosphate (ThDP)-dependent enzyme that catalyzes the nonoxidative decarboxylation of benzoylformate yielding benzaldehyde and carbon dioxide. A large model of the active site is constructed on the basis of the X-ray structure, and it is used to characterize the involved intermediates and transition states and evaluate their energies. There is generally good agreement betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 74 publications
3
36
0
Order By: Relevance
“…Models B – E represent the cofactor in the BFDC active site in the absence and presence of bound ligands. The active site model is built on the basis of the crystal structure (PDB ID 1MCZ) and is identical to that used in the mechanistic study [29]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Models B – E represent the cofactor in the BFDC active site in the absence and presence of bound ligands. The active site model is built on the basis of the crystal structure (PDB ID 1MCZ) and is identical to that used in the mechanistic study [29]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, a similar approach was used to characterize the nucleophilicity of the N1′ and N4′ centers [24]. In many cases, rather than simply focus on the cofactor, computational studies have been used to investigate full reaction mechanisms of ThDP enzymes, including pyruvate decarboxylase (PDC) [2528], benzoylformate decarboxylase (BFDC) [2930], acetohydroxy acid synthase [24,3135], pyruvate dehydrogenase (PDH) [36], benzaldehyde lyase [37], cyclohexane dione hydrolase [38], oxalyl-CoA decarboxylase [39], DXP synthase [40] and transketolase [4142].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further mutational studies showed that the effect of replacement of His-281 or His-70 on catalysis is dependent on the amino acid substituted (40). Further work using density functional theory calculations highlighted the probability that His-70, 281 and Ser-26 are all involved in substrate binding via hydrogen bonding (41).…”
Section: Comparison With Other Thdp-dependent Enzymesmentioning
confidence: 99%